Kebudayaan Bagi Pekabaran Injil - Juanda Yulianus (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2022)
Culture in each region has its own characteristics. But these characteristics do not limit the evangelism is carried out through and within culture. Culture as access in evangelism. The relationship between culture and evangelism is that the evangelist understands the culture and thoughts or beliefs of the local community, then finds the right method to carry out the evangelism. The discussion of this research uses a qualitative method, namely the study of literature. Understanding culture for evangelism is summarized and is a literature study by reading books related to culture for evangelism so that it becomes a new and useful discovery